The world’s first “Smart Nation” vision: the case of Singapore - Esra Banu SIPAHI; Zabihullah SAAYI (Smart Cities and Regional Development Journal)
“Smartization” is the policy that Singapore as a city-state with a small geographical territory, limited natural resources, increasing urban density and aging population but determined to become an exceptional city-state has adopted to overcome various national challenges, improve the quality, efficiency and performance of urban services, sustainable development and overall improvement of citizens’ lives. In this regard, the Smart Nation initiative, which has been undertaken in late 2014 is considered a turning point that aims to make Singapore the first smart nation or the first smart country (mega-smart city) in the world. This paper is dedicated to the study of Singapore’s digitization process, especially the initiative of Smart Nation, which is an upgraded version of the smart city. In the framework of this article, the factors of Singapore’s transition to the digitization process, especially the Smart Nation initiative, are discussed, the plans and programs related to this process and the country’s achievements in this direction are explained. Meanwhile, along with all the achievements, the challenges, limitations and problems of the initiative of forming the Smart Nation have been pointed out.